2018
DOI: 10.1177/0394632017750518
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of ferulic acid attenuates inflammation and oxidative stress in a rat model of lipopolysaccharide-induced acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a fatal clinical condition that can be caused by pulmonary and non-pulmonary diseases. Oxidative stress and inflammation play key roles in the development of ARDS. In this study, we investigated whether ferulic acid (FA), an anti-oxidant, was beneficial for prophylaxis of ARDS. We established an ARDS rat model using lipopolysaccharide (LPS) administration. Lung injury was assessed by lung wet/dry ratio and broncho-alveolar lavage fluid (BALF) analysis. Hematoxylin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
(39 reference statements)
3
30
0
Order By: Relevance
“…In LPS-stimulated RAW 264.7 cells, 100 mM FA reduces the translocation of NF-E2-related factor 2 (Nrf2) and nuclear transcription factor-kB (NF-kB) into the nuclei through a reduction of the expression of phosphorylated IKK and consequently inhibits proinflammatory IL-6 production (Lampiasi and Montana, 2016;Lampiasi and Montana, 2018). FA down-regulates mitogen-activated protein kinase signaling (p38, ERK and JNK) and reserved the antioxidant activity in the injured lungs induced by LPS stimulation (Zhang et al, 2018). Several studies also demonstrated that FA may target Toll-like receptor 4 (TLR4) to inhibit LPS infection.…”
Section: Discussionmentioning
confidence: 99%
“…In LPS-stimulated RAW 264.7 cells, 100 mM FA reduces the translocation of NF-E2-related factor 2 (Nrf2) and nuclear transcription factor-kB (NF-kB) into the nuclei through a reduction of the expression of phosphorylated IKK and consequently inhibits proinflammatory IL-6 production (Lampiasi and Montana, 2016;Lampiasi and Montana, 2018). FA down-regulates mitogen-activated protein kinase signaling (p38, ERK and JNK) and reserved the antioxidant activity in the injured lungs induced by LPS stimulation (Zhang et al, 2018). Several studies also demonstrated that FA may target Toll-like receptor 4 (TLR4) to inhibit LPS infection.…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatments were administered once daily for 28 days. The dose of FA (60 mg/kg) was based on the following studies (Mancuso et al, 2014;Hassanzadeh et al, 2017;Zhang et al, 2018)with a modification. There was no effect of pre-treatment with ferulic acid (50 mg/kg), but there were significant effects at doses of 75 mg/kg and 100 mg/kg, and there were no differences between these two doses (Mancuso et al, 2014;Hassanzadeh et al, 2017).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Fifty mg/kg FA caused the attenuation of inflammation in lipopolysaccharide-induced rat acute respiratory distress syndrome (Zhang et al, 2018). The time of FA pre-treatment and the treatment duration were based on a previous study (Hassanzadeh et al, 2017), but our treatment period was 10 days longer than their 18-day treatment, as they failed to show an improvement of locomotive activities.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Recent studies have suggested that C3G potentially exerts functions primarily through C3G metabolites (C3G-Ms) [7], and more than 20 kinds of C3G-Ms have been identified in serum by a pharmacokinetics study in humans [8]. Although the function and mechanism of C3G-Ms are still not clear, protocatechuic acid (PCA) [9][10][11][12], phloroglucinaldehyde (PGA) [1], vanillic acid (VA) [13][14][15], ferulic acid (FA) [16][17][18][19], and their derivates represent the main bioactive metabolites of C3G due to their antioxidant and anti-inflammatory properties. Figure 1.…”
Section: Introductionmentioning
confidence: 99%